2010
DOI: 10.1590/s0101-20612010000500014
|View full text |Cite
|
Sign up to set email alerts
|

Análise sensorial de caldos e canjas elaborados com farinha de carcaças de peixe defumadas: aplicação na merenda escolar

Abstract: A tilápia do Nilo (Oreochromis niloticus) é o peixe mais cultivado em quase todo Brasil, com mais de 38% do total produzido; seguida das carpas e dos peixes redondos (tambaqui, pacu e tambacu), ambos representando em torno de 25% (IBAMA, 2005).Apesar do grande mercado consumidor, o país apresenta um dos menores índices de consumo per capita de pescado do mundo, tendo apenas a décima posição na América do Sul (FAO, 2005). A média nacional é de 7 a 8 kg/hab/ano, quase a metade do recomendado pela Organização Mun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
18

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 3 publications
0
11
0
18
Order By: Relevance
“…Technology Maringá, v. 39, suppl., p. [525][526][527][528][529][530][531]2017 in polyunsaturated fatty acids, mainly the ones from omega-6 series (n-6) and omega-3 (n-3), such as arachidonic acid (ARA or C20:4n-6) and the eicosapentaenoic acid (EPA or C20:5n-3) respectively, with EPA being able to originate docosahexaenoic (DHA or C22:6n-3) (Tapiero, Nguyen, Couvreur, & Tew, 2002, Tocher, 2003. The usage of waste generated by fish industry in Brazil is very low (Godoy et al, 2010) and the quantity of produced residue is significant, varying from 8 to 16% when the final product is gutted fishery or 60 to 72% when the final product is skinless fillet (Kubitza & Campos, 2006). These residues present great quantity of material rich in protein, which are usually converted into products for animal nutrition, such as meals and fertilizers of low market value (Chalamaiah, Kumar, Hemalatha, & Jyothirmayi, 2012), fish oil, protein concentrates, surimi, pâtés, silage, among others (Morales-Ulloa & Oetterer, 1995, Bimbo, 2000.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Technology Maringá, v. 39, suppl., p. [525][526][527][528][529][530][531]2017 in polyunsaturated fatty acids, mainly the ones from omega-6 series (n-6) and omega-3 (n-3), such as arachidonic acid (ARA or C20:4n-6) and the eicosapentaenoic acid (EPA or C20:5n-3) respectively, with EPA being able to originate docosahexaenoic (DHA or C22:6n-3) (Tapiero, Nguyen, Couvreur, & Tew, 2002, Tocher, 2003. The usage of waste generated by fish industry in Brazil is very low (Godoy et al, 2010) and the quantity of produced residue is significant, varying from 8 to 16% when the final product is gutted fishery or 60 to 72% when the final product is skinless fillet (Kubitza & Campos, 2006). These residues present great quantity of material rich in protein, which are usually converted into products for animal nutrition, such as meals and fertilizers of low market value (Chalamaiah, Kumar, Hemalatha, & Jyothirmayi, 2012), fish oil, protein concentrates, surimi, pâtés, silage, among others (Morales-Ulloa & Oetterer, 1995, Bimbo, 2000.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies were conducted in order to develop fish meals for human consumption (Franco et al, 2009, Godoy, Franco, Souza, Stevanato, & Visentainer, 2013, by adding it in products like cookies and biscuits (Franco et al, 2013), snacks (Justen et al, 2011), stocks and soups (Godoy et al, 2010), among others. This inclusion was considered viable to increase nutritional value of products; apart from the fact that developing products with addition of fish and its derivatives is a way of supporting this product consumption and incrementing fishery productive chain.…”
Section: Introductionmentioning
confidence: 99%
“…Apesar desses benefícios, observa-se a pouca oferta de alimentos à base de pescado nas escolas do Rio Grande do Sul 15 . No entanto, alguns estudos 6,16,17 demonstram que a introdução de produtos à base de peixe na alimentação escolar é uma alternativa viável, corroborando os resultados desta pesquisa.…”
Section: Discussionunclassified
“…Apesar de seus benefícios comprovados à saúde, o Brasil apresenta um dos menores índices de consumo per capita de pescado do mundo. A média de consumo nacional é de 7 a 8 kg/hab/ano, inferior ao recomendado pela Organização Mundial da Saúde, que é de 12 kg/hab/ano, e à média mundial de 15,8 kg/hab/ano 6 . Em relação à média de consumo do pescado na alimentação escolar, o per capita é de apenas 41,4 g/aluno/refeição 7 .…”
Section: Introductionunclassified
“…These pasta products, such as lasagna, can have their nutritional value increased by adding non-traditional ingredients to their formulation without apparent loss of quality (Petitot et al, 2010). Several studies have shown that the inclusion of protein concentrates from fish or fish meal into sweet and savory products can increase the nutritional value of the product (Ibrahim, 2009;Godoy et al, 2010;Coradini et al, 2015), including of pasta .…”
Section: Introductionmentioning
confidence: 99%